Genome-Editing Technologies for Enhancing Plant Disease Resistance - Andolfo, Giuseppe; Iovieno, Paolo; Frusciante, Luigi; Ercolano, Maria R. (Frontiers in Plant Science, 2016)
One of the greatest challenges for agricultural science in the 21st century is to improve yield stability through the progressive development of superior cultivars. The increasing numbers of infectious plant diseases that are caused by plant pathogens make it ever more necessary to develop new strategies for plant disease resistance breeding. Targeted genome engineering allows the introduction of precise modifications directly into a commercial variety, offering a viable alternative to traditional breeding methods. Genome editing is a powerful tool for modifying crucial players in the plant immunity system. In this work we propose and discuss genome-editing strategies and targets for improving resistance to phytopathogens. First of all, we present the opportunities to rewrite the effector-target sequence for avoiding effector-target molecular interaction and also to modify effector-target promoters for increasing the expression of target genes involved in the resistance process. In addition, we describe potential approaches for obtaining synthetic R-genes through genome-editing technologies (GETs). Finally, we illustrate a genome editing flowchart to modify the pathogen recognition sites (PRSs) and engineer an R-gene that mounts resistance to some phylogenetically divergent pathogens. GETs potentially mark the beginning of a new era, in which synthetic biology affords a basis for obtaining a reinforced plant defense system. Nowadays it is conceivable that by modulating the function of the major plant immunity players, we will be able to improve crop performance for a sustainable agriculture.